Sinus Radiological Findings in General Asymptomatic Populations: A Systematic Review of Incidental Mucosal Changes. (July 2022) - Razi, Basil; Perkovic, Adam; Alvarado, Raquel; Stroud, Anna; Ho, Jacqueline; Kalish, Larry H.; Campbell, Raewyn G.; Sacks, Raymond; Harvey, Richard J.
Objective: To determine the range of incidental mucosal changes in a general sinonasally asymptomatic population on radiology. Data Sources: Medline (1996-present) and Embase (1974-present) were searched on March 14, 2020, to identify articles that reported radiological sinus mucosal findings in asymptomatic population groups. Bibliographic search of included studies was conducted to identify additional articles. Review Methods: The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and Cochrane Handbook for Systematic Reviews of Interventions. A comprehensive search strategy was formulated and articles screened to extract data reporting Lund-Mackay (LM) score, presence of mucous retention cysts, and maxillary mucosal thickening. A random-effects model was used in meta-analysis. Results: A total of 950 articles were identified, of which 33 manuscripts met the inclusion criteria. The included studies involved 16, 966 sinonasally asymptomatic subjects. The mean LM score was 2.24 (95% CI, 1.61-2.87), and an LM score of ≥4 in 14.71% (95% CI, 6.86-24.82%) was present across all general asymptomatic population groups. Mucous retention cysts were noted in 13% (95% CI, 8.33-18.55%) and maxillary mucosal thickening of ≥2 mm in 17.73% (95% CI, 8.67-29.08%). Conclusion: The prevalence of incidental mucosal changes in a general asymptomatic population on radiology needs to be considered when making a diagnosis of chronic rhinosinusitis.